Radiation Dose Measurements at Radiosensitive Organs in Overcouch Barium Enema Examination - Farah Mardhiah Janudin; Akmal Sabarudin; Khadijah Mohamad Nassir (Journal of Medical Physics and Biophysics, 2017)
The objectives of this study were to measure the radiation dose on the skin surface at the selective radiosensitive organs and to compare its distributions on an anthropomorphic phantom during an overcouch barium enema examination. This study was also designed to suggest the suitable exposure parameters for the projections in overcouch barium enema examination. The eye lens, thyroid, breast, and gonad were selected in this study and the dose was measured using thermoluminesence dosimeters (TLD) with computed radiography system. Five radiographic projections were carried out including supine, prone, right lateral decubitus, left lateral decubitus, and prone-angled view (Hampton’s view) to demonstrate the entire lower gastrointestinal tract. The highest skin surface dose (SSD) was received at the gonad followed by breasts, lens, and thyroid, corresponding to 2.49 ± 1.32 mGy, 0.14 ± 0.08 mGy, 0.057 ± 0.032 mGy, and 0.044 ± 0.04 mGy, respectively. The exposure parameters for tube voltage in a range of 75 kVp to 80 kVp, and tube current between 36 mAs and 40 mAs can provide proper image quality for abdominal region for an individual with average body weight.